Masones y Sociedades Secretas: redes militares durante las guerras de independencia en América del Sur - Felipe Santiago del Solar (Les Cahiers ALHIM)
The historiography that has given account of the masonic participation during the South American Independences, has been suspended during almost two centuries in the dichotomy apologist/detractive or in the structure mystification/demystification. Our article intends to analyze the historiographic production developed to that matter and to propose a new view of analysis complementary to the traditional one, that will allow us to understand the implantation of lodges as a process of Atlantic circulation that owns its particular rhythm and characteristics.